Mapping the dimensions of electronic service quality with electronic customer relationship management (e-CRM) features for electronic reservation / Zazaleena Zakariah, Nursyahidah Alias and Norhafizah Hashim - Zakariah, Zazaleena; Alias, Nursyahidah; Hashim, Norhafizah (2009)
With the growth of electronic commerce (e-commerce), electronic service (e-service) is becoming important for supplementing e-commerce functions as customers require a high quality of services in electronic market. Researcher shows, hotels that adopt e-CRM solutions would expect that the application improve their operational effectiveness and therefore deliver value to the organizations. This paper addresses the mapping of the dimensions of e-service quality with electronic customer relationship management (e-CRM) features for electronic reservation in hotel services. In this study, dimension of e-service quality is conceptualized based on the literature review of the e-CRM features. Our study suggests that the service quality of both incubative dimension and active dimension are important for hotel services to attract customers in the electronic market. In this study, the mapping process is based on 42 e-CRM features. It illustrate that different dimension of e-service quality are of different importance in electronic reservation. Furthermore, it is implied in this study that reliability, efficiency, support, communication, security, incentive, ease of use, linkage and information are vital for electronic reservation in hotel services.